Research on Rapid Evaluation of Rock Mass Quality Based on Ultrasonic Borehole Imaging Technology and Fractal Method - Yuezheng Zhang; Hongguang Ji; Wenguang Li; Kuikui Hou (Advances in Materials Science and Engineering)
The distribution of discontinuities in the deep stratigraphic rock mass is random and irregular, and the spatial distribution has statistical self-similarity, which can be analyzed by fractal theory. The borehole wall image obtained based on the ultrasonic borehole imaging technology can clearly reflect the rich structural surface information such as the inclination, density, and crack width of the structural surface in the rock mass. Due to its inherent fractal characteristics, the fractal box dimension of the hole wall image can be used to describe the complexity of the structural surface. In the study, the fractal box dimension of the hole wall image and the RQD value of the rock mass are compared, and it is found that there is a linear correlation between the two. Therefore, the rock quality can be evaluated according to the fractal box dimension value of the hole wall image. Finally, a rapid quantitative evaluation method for rock mass quality classification is established based on ultrasonic borehole imaging technology and fractal method.